Factors that hinder organ donation: religio-cultural or lack of information and trust - Tumin, M.; Noh, A.; Jajri, I.; Chong, C.S.; Manikam, R.; Abdullah, N. (2013)
Objectives: This paper examines factors that influence Malaysian persons with a tertiary level of education on their willingness to donate organs. Materials and Methods: A survey was done in the Klang Valley (Kuala Lumpur and its suburbs) at several designated locations. A total of 1420 people were approached, and we focused the sample of 688 respondents with a tertiary level of education. Respondents were given 2 sets of answers: (1) a religio-cultural category and (2) a structural category. They were allowed to choose more than 1 reason. Results: Our findings revealed that only 47.5 percent of respondents declined becoming organ donors. The highest frequency recorded was "I am not convinced that my body part will be used beneficially" (30.1), followed by "I do not have enough access to information" (292), "I want my body to remain intact after death" (16.9), and "It is against my religion" (9.9). Conclusions: Our study revealed that religio-cultural factors are not a prime explanation for the lack of organ donation in the Malaysian case. This study suggests that better procurement methods used by dedicated agencies, as well as better education, could reduce the shortage between organ supply and demand.